Aniridia associated with microcornea and subluxated lenses. Issue 2 (February 1978) - David, R; MacBeath, L; Jenkins, T
Abstract : Four cases of aniridia associated with subluxated lenses and microcornea are presented. The triad occurred in both eyes of the 4 affected members in one Ndebele family (one of the South African Negro tribes). No other ocular or systemic defects were noted, and intelligence was normal. Chromosomal studies on both parents showed no abnormality, and gene marker studies failed to reveal any linkage between the disease locus and a wide range of polymorphic loci.